Assessing the rights of the indigenous child to education - a case study of the Batwa in Uganda - Twinomugisha, Ben Kiromba (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.